Optimizing acromioclavicular joint management: A case series on minimally invasive TightRope with double endobutton fixation - Bharath Vadivel Kumar; Prem Kumar Kothimbakkam; Vijayashankar Murugesan (Asian Journal of Medical Sciences, 2024)
Acromioclavicular (AC) joint dislocation constitutes 40% of shoulder injuries, impacting patients across diverse activities. The Rockwood Staging System guides assessment, prompting exploration of the novel TightRope with double endobutton fixation technique to restore AC joint function. This study aims to evaluate the outcomes of the TightRope with double endobutton fixation technique in 20 cases of AC joint dislocation, emphasizing its potential advantages over conventional methods. A case series involving 20 AC joint dislocation cases underwent comprehensive evaluation, including follow-ups and radiological assessments. Surgical interventions were performed using the TightRope with double endobutton fixation technique. The average age was 44.5 years, with a notable prevalence of severe dislocations (Classes V and VI). Surgical interventions demonstrated efficiency, with a brief hospital stay. The innovative technique yielded excellent outcomes, with 90% achieving high Constant–Murley scores. TightRope with double endobutton fixation emerges as a promising, minimally invasive strategy for AC joint dislocation, exhibiting potential in minimizing post-operative complications and expediting recovery. The study advocates for individualized interventions and emphasizes the need for further exploration of long-term implications.